Peer influence on form 4 students' motivation towards English learning / Nor Izni Mohd. Hassan - Mohd. Hassan, Nor Izni (Faculty of Education, 2011)
This study was carried out to investigate the influence peers have on Form 4 students’ motivation towards English learning. A total of seventy five Form Four students from an urban area in Selangor were selected based on convenient sampling as the respondents of the study. A set of questionnaire was designed to gain primary data from the respondents on the peer influence on their motivation towards English learning. The overall findings of this study indicate that peers’ socioeconomic status does not affect students’ motivation towards English learning. This is because, parents regardless of income and occupations view English as important and encourage their children to excel in the subject. These peers then influence the students in English learning. Peers’ race and ethnicity are revealed to have influence on students’ motivation towards English learning. Peers of the same race can lead to The Bad Apple Model and in the same time encourage collaborative learning when they assist one another in explaining unfamiliar English vocabulary. Apart from that, the findings also show that peers’ gender does influence students’ motivation towards English learning. Female peers are claimed to be better behaved and more focused in the classroom. They are also very helpful during English lessons and are the ones who score better grades in English. The findings also revealed that male peers are the ones who contribute to fun and interactive English learning atmosphere. In conclusion, the recommendation for future research in this field has been inserted in the final part of the study.